Means of calling the Messengers: An analytical study of the calling of the Prophet of God, Abraham, peace be upon him - Al-Ahmari, Haila Ali Mohammed; Al-Zamli, Ahmed Ali (Journal of Humanities & Social Sciences, 2024)
This academic study titled "The Methods of Prophets’ Call: An Analytical Study of the Call of Prophet Ibrahim (PBUH)" aims to analyze the missionary methods used by Prophet Ibrahim (PBUH) in his call to the oneness of Allah and sincere worship. The study seeks to clarify and detail these methods, such as wisdom, good exhortation, establishing proof, and patience in the face of harm, by exploring their effective role in achieving the objectives of the call. Additionally, the study aims to provide recommendations for applying these methods in the contemporary missionary context, enhancing understanding and enabling effective applications in modern society. The study includes an in-depth analysis of the missionary methods of Prophet Ibrahim (PBUH), including wisdom, good exhortation, establishing proof, and patience in the face of harm. It also examines the contemporary applications of these methods and how to utilize them in modern missionary work. The results showed that Prophet Ibrahim (PBUH) used various methods in his call, such as rational dialogue, establishing proof, and patience in the face of harm, which had a significant impact on spreading his message and the oneness of Allah. The study confirmed that applying these methods in contemporary missionary work can enhance the effectiveness and success of the call in modern society. The lessons drawn highlight the importance of ethics in missionary work and the study of the lives of the prophets as a source of inspiration and education. The study adopted the inductive analytical method to analyze and establish legal issues, based on religious texts and rational evidence.